2008
DOI: 10.1063/1.2966578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of absorbed water components on SiOCH low-k reliability

Abstract: We investigated plasma treatment induced water absorption in a SiOCH low-k dielectric and the influence of the absorbed water components on the low-k dielectric reliability. By using thermal desorption spectroscopy (TDS), water absorption in SiOCH was evidenced for N2/H2 plasma treatments. Based on these TDS results, two anneal temperatures were selected to separate and quantify the respective contributions of two absorbed water components, physisorbed (α) and chemisorbed (β) water, to low-k dielectric reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 12 publications
2
52
0
Order By: Relevance
“…49 An annealing step is supposed to remove moisture and improve the film reliability. However, Li et al 50 suggested that the removal of physisorbed water by baking at 190…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…49 An annealing step is supposed to remove moisture and improve the film reliability. However, Li et al 50 suggested that the removal of physisorbed water by baking at 190…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…The need for the DB to block H 2 O/O 2 in-diffusion is due to the demonstrated ability of low-k a-SiOC:H ILD materials to readily uptake moisture [280][281][282][283][284] and the many deleterious resulting effects that have been reported. Specifically, moisture and O 2 permeation into a metal interconnect structure has been shown to result in a number of effects ranging from increased ILD viscoplasticity, 285 dielectric constants, [286][287][288] and leakage currents [289][290][291] to reduced ILD fracture strength, [292][293][294][295][296] ILD/DB adhesion, 297-299 DB/metal adhesion, 300 TDDB lifetimes, 301,302 and electromigration lifetimes. 303,304 Some of the above reliability issues, such as ILD/DB and DB/metal adhesion and electromigration, have been directly linked to H 2 O/O 2 diffusion through the DB and oxidation of the underlying metal and via/trench barrier.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (1) N30mentioning
confidence: 99%
“…The adsorbed water molecules degrade dielectric constant and electrical reliability of low-k materials. 29 Absorption peaks from residual organic template and CH 2 groups from bridging organic groups are located between 3000 and 2750 cm −1 . No adsorbed water molecules (3700-3000 cm −1 ) are observed in the spectra of all pristine films (see the inset at the Figure 2).…”
Section: Resultsmentioning
confidence: 99%